(untitled) (Sysney, Australia, 1992)
Science in society is a text designed specifically for the revised Queensland Multi-Strand Science syllabus; but it will have widespread application to general science course throughout Australia. This text show senior students the relevance of science in their own lives through topics that will stimulate their interest, accompanied by a wide range of exercises, activities and investigation.
Keywords: Science,Science,Khoa học,Khoa học